Clinical course, pathological correlations, and outcome of biopsy proved inflammatory demyelinating disease. Issue 12 (16th November 2005) - Pittock, S J; McClelland, R L; Achenbach, S J; Konig, F; Bitsch, A; Brück, W; Lassmann, H; Parisi, J E; Scheithauer, B W; Rodriguez, M; Weinshenker, B G; Lucchinetti, C F
Abstract : Background: A pathological classification has been developed of early active multiple sclerosis (MS) lesions that reveals four patterns of tissue injury: I—T cell/macrophage associated; II—antibody/complement associated; III—distal oligodendrogliopathy, and IV—oligodendrocyte degeneration in the periplaque white matter. Mechanisms of demyelination in early MS may differ among the subgroups. Previous studies on biopsied MS have lacked clinicopathological correlation and follow up. Critics argue that observations are not generalisable to prototypic MS. Objective: To describe the clinicopathological characteristics of the MS Lesion Project biopsy cohort. Methods: Clinical characteristics and disability of patients with pathologically confirmed inflammatory demyelinating disease (excluding ADEM) classified immunopathologically (n = 91) and patients from the Olmsted County MS prevalence cohort (n = 218) were determined. Results: Most patients who underwent biopsy and had pathologically proved demyelinating disease ultimately developed definite (n = 70) or probable (n = 12) MS (median follow up 4.4 years). Most had a relapsing remitting course and 73% were ambulatory (EDSS ⩽4) at last follow up. Nine patients remained classified as having an isolated demyelinating syndrome at last follow up. Patients with different immunopathological patterns had similar clinical characteristics. Although presenting symptoms and sex ratios differed, the clinical course in biopsy patients was similar to the prevalence cohort. Median EDSS was <4.0 in both cohorts when matched for disease duration, sex, and age. Conclusions: Most patients undergoing biopsy, who had pathologically confirmed demyelinating disease, were likely to develop MS and remain ambulatory after a median disease duration of 4.4 years. The immunopathological patterns lacked specific clinical correlations and were not related to the timing of the biopsy. These data suggest that pathogenic implications derived largely from MS biopsy studies may be extrapolated to the general MS population.